The pros and cons of rent-seeking: Political rent in various research paradigms - Stefan Sękowski (Studia z Polityki Publicznej, 2021)
This article shows that how we look at political rent and rent-seeking depends on our position on state interference in the economy and which theory of regulation we are familiar with. Although the theory of rent-seeking is in accordance with the paradigm of the private interest (economic) theories of regulation, the researcher also needs an insight based on the public interest theories of regulation if he wants to judge the impact of rent-seeking and the creation of political rent on social well-being properly. The paper is also a conceptualization of political rent. It describes forms of rent-seeking and economic systems most amenable to it.